2012
DOI: 10.1007/s00535-012-0672-2
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic esophagitis distinguishes patients with non-erosive reflux disease from those with functional heartburn

Abstract: The lack of ME in the esophageal distal biopsies of FH patients indicates a limited role of these histological abnormalities in symptom generation in them. ME can be considered as an accurate and reliable diagnostic marker for distinguishing FH patients from GERD patients and has the potential to be used to guide the correct therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
136
2
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(154 citation statements)
references
References 30 publications
5
136
2
11
Order By: Relevance
“…However, they also showed that physicians often do not pay attention to a negative pH study continuing to prescribe PPIs and even sending their patients to antireflux surgery, as already observed in our previous study. 28 Furthermore our findings suggest that previous studies looking at morphological and/or pathophysiological differences between FH and NERD, diagnosed with 24-hour pH/pH-impedance studies, [10][11][12][13][14] may have been inaccurate. Structural characteristics, which are devoid of day to day fluctuations, ie, histopathological parameters or basal impedance, could be the best variables in order to diagnose FH, but their diagnostic performance needs to be evaluated against a gold standard.…”
Section: Discussionmentioning
confidence: 69%
“…However, they also showed that physicians often do not pay attention to a negative pH study continuing to prescribe PPIs and even sending their patients to antireflux surgery, as already observed in our previous study. 28 Furthermore our findings suggest that previous studies looking at morphological and/or pathophysiological differences between FH and NERD, diagnosed with 24-hour pH/pH-impedance studies, [10][11][12][13][14] may have been inaccurate. Structural characteristics, which are devoid of day to day fluctuations, ie, histopathological parameters or basal impedance, could be the best variables in order to diagnose FH, but their diagnostic performance needs to be evaluated against a gold standard.…”
Section: Discussionmentioning
confidence: 69%
“…It has been revealed that RH is more likely to present with esophageal mucosal changes than FH. 26 Furthermore, RH may respond less well than real NERD, so separating RH from real NERD and FH is of clinical significance. The current study also focused on the motility characteristics of heartburn patients.…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be assumed as the consequence of the dilation of intercellular space diameters of the oesophageal mucosa in GERD patients, demonstrated in patients with or without pathological acid exposure time, and allows to confirm the diagnosis of GERD even when the other MII-pH variable are within the normal range. 25,26 In the present investigation, efforts were also focused to prospectively evaluate, in CC patients, the role of MII-pH variables in predicting PPI response. Responder CC patients were frequently characterised by pathological AET and/or lower IB values as well as by the concomitant presence of typical symptoms.…”
Section: Discussionmentioning
confidence: 99%